PENGARUH UTANG LUAR NEGERI, CADANGAN DEVISA, DAN INVESTASI ASING TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA TAHUN 1991-2021 - Rahayuningsih, Istiqo; Murtala, Murtala; Rahmah, Mutia (Jurnal Ekonomi Regional Unimal, 2023)
This research aims to determine the influence of Foreign Debt, Foreign Exchange Reserves and Foreign Investment on Economic Growth in Indonesia in 1991-2021. This research uses secondary data in the form of a time series for 31 years with the Autoregressive distributed lag (ARDL) test analysis method. The results of this research show that Foreign Debt has a negative and significant effect in the long term and short term on Economic Growth, Foreign Exchange Reserves has a positive and insignificant effect in the short term but in the long term it has a positive and significant effect, while Foreign Investment has no effect in the short term and long-term impact on economic growth in Indonesia. The recommendation in this research is that the government needs to manage foreign debt wisely by considering long-term risks and benefits and ensuring that loans are used for productive investments that can increase economic growth.